Komparasi Perhitungan Kadet Secara Manual Dan Dengan Menggunakan Program – Program Pelayaran Dalam Pelaksanaan Passage Plan - Samsul Huda; Firdaus Sitepu; Vitrianna Sulistyaningrum; Gilang Pambudi Supar (Politeknik Ilmu Pelayaran Semarang, 2021)
To improve the academic ability of a cadet, it is necessary to apply the principles of shipping with the use of computer technology which is accommodated by existing shipping programs on board. In the implementation of a voyage, it always uses a passage plan to make it easier to navigate either flat or electronically. A cadet must really be equipped with the ability to calculate manually and the ability to understand the use of shipping tables and be able to apply it in a computer program. The research method is descriptive. Data collection was carried out by manual calculation of the concept of Flat Sailing using a Mercator map and comparison of the results of calculations with programs on the ship, observation, structured interviews, documentary studies and library research. The purpose of this study was to compare the results of manual calculations and by using shipping programs carried out by cadets in the implementation of the Passage Plan. The results showed that the cadets still did not understand the application of cruise calculation formulas on the projection of the mercator chart or mercator map. Cadets in entering data in a program are still wrong and less thorough so that it will affect the implementation of the passage plan.